The World Conference against Racism: What Was Really Achieved - Leaphart, Jerry V. (Tufts Archival Research Center, 2005)
Volume 26, Issue 2. Summer/Fall The WCAR process was far more successful and important than most critics realize, writes a civil rights lawyer who attended the events.